FAO fisheries circular; No.914 - FAO (FAO, 1996)
The book lists a total of 262 fish, crustacean and mollusc species, representing the most important aniaml used in aquaculture worldwide. For each one of the listed species, family, scientific name, common name, environment, total production, geographical distribution by continent are given